2014
DOI: 10.1002/adfm.201400524
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Silica Nanoparticles: Selective Surface Functionalization for Optimal Relaxometric and Drug Loading Performances

Abstract: Mesoporous silica nanoparticles (MSNs) have emerged as promising biomaterials for drug delivery and cell tracking applications, for which MRI is the medical imaging modality of choice. In this contribution, MRI contrast agents (DTPA‐Gd) and polyethylene glycol (PEG) are grafted selectively at the surface of MSNs, in order to achieve optimal relaxometric and drug loading performances. In fact, DTPA and PEG grafting procedures reported until now, have resulted in significant pore obstruction, which is detrimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
88
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 90 publications
4
88
0
Order By: Relevance
“…An important finding was the observation of enhanced relaxivity for Gd III chelates selectively linked to the external surface of the MSNs, and this behaviour was associated with limited water diffusion inside the pores, as this prevents the efficient transfer of the paramagnetic effect to the bulk water. Furthermore, other relevant studies on Gd‐based MSNs for MRI or theranostic applications have been reported in recent years . It should be emphasized that the great majority of the considered complexes are represented by functionalized GdDTPA or GdDTPA‐monoamide chelates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important finding was the observation of enhanced relaxivity for Gd III chelates selectively linked to the external surface of the MSNs, and this behaviour was associated with limited water diffusion inside the pores, as this prevents the efficient transfer of the paramagnetic effect to the bulk water. Furthermore, other relevant studies on Gd‐based MSNs for MRI or theranostic applications have been reported in recent years . It should be emphasized that the great majority of the considered complexes are represented by functionalized GdDTPA or GdDTPA‐monoamide chelates.…”
Section: Introductionmentioning
confidence: 99%
“…(A) Schematic view of the synthetic pathway for Gd 2 L 2 ‐MSN‐PEG and the structure of Gd 2 L 1 . (B) HRTEM micrographs of the MSN sample at low and high magnifications.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the loading capability of FA-MSN-DEX is still higher than that of several recently reported silicabased delivery systems [ 41,42 ] and an optimal balance between effective targeting and high drug loading may be achieved by further tuning the quantity of the functional groups. [ 43 ] In vitro release tests show that the three kinds of MSNs display similarly sustained and pH-dependent release profi les with faster drug release at pH 5.0 than at pH 7.4, which could be attributed to the increased solubility of DOX at lower pH ( Figure S12, Supporting Information). [ 44 ] Besides, the surface-modifi ed samples show lower DOX release rate compared to pMSN, which suggests the functional groups on the external surface may also affect the outward diffusion of DOX.…”
mentioning
confidence: 95%
“…Results clearly showed a pH dependent release of DOX (Figure S3b) from the Nano‐IRIS over time. In acidic conditions, the SiO − groups present in silica framework gets protonated and induce the release of DOX from the silica surface, whereas at normal pH (pH=7.4) the silica surface predominantly stays as SiO − which strongly interacts with the DOX and keep it intact on the surface, thereby minimizing its release …”
Section: Resultsmentioning
confidence: 99%